Barbarzyńcy w "Vita Epifani" Ennodiusza z Pawii - Skibiński, Tomasz (Vox Patrum, 2019)
The article presents the image and the place of barbarians in the late-Roman society in the light of Vita Epifani by Ennodius (Magnus Felix Ennodius). The analysis of the work, and above all the diplomatic missions carried out by Bishop Epiphanius, shows the world of the second half of the 5th century, co-created by Romans and the barbarians, in which the latter have their inalienable place. They are no longer guests and newcomers, but co-hosts and co-creators of the new community of the late antiquity. Ennodius’ work appears as a call to the Roman clergy and aristocracy to work together with the new peoples present in the former Roman territories, and with their rulers. The work also presents a new image of the episcopal ministry, focused on building a new community gathering the Romans and the barbarians. Ennodius, a bishop-diplomat, carries out religious activities, while avoiding the controversial issues concerning relations with Arianism. He emphasises social and political activity in the face of a weakening civilian authority.